2019
DOI: 10.24259/fs.v3i2.7050
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of forest to rural households’ livelihood: evidences from Da river basin in the northwest mountainous region of Vietnam

Abstract: This paper examined how forest has contributed to rural households’ livelihood in Da river basin, the northwest mountainous region of Vietnam. The results revealed that forest predominantly contributes to the total income of rural residents in the region. Specifically, forestry land area, access to non-timber forest products, and payment for forest environmental services significantly affected household’s income in the region. However, rural people in the region have still faced several difficulties that const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The supply of ES can be affected by numerous drivers of change that can be divided into the categories of direct (e.g., harvesting, land-coverchange) and indirect (e.g., cultural or religious issues, economic change, climate change). Among the human-induced indirect drivers, economic conditions have been highlighted as the most significant factors that induce changes in land cover (Chu et al, 2019).…”
Section: Socio-demographic Factors Undermining the Factor Influencing...mentioning
confidence: 99%
“…The supply of ES can be affected by numerous drivers of change that can be divided into the categories of direct (e.g., harvesting, land-coverchange) and indirect (e.g., cultural or religious issues, economic change, climate change). Among the human-induced indirect drivers, economic conditions have been highlighted as the most significant factors that induce changes in land cover (Chu et al, 2019).…”
Section: Socio-demographic Factors Undermining the Factor Influencing...mentioning
confidence: 99%
“…The high belief of community forest farmers in Indonesia agrees with the findings of other studies. Chu et al (2019) reported that forests contribute significantly to livelihoods, especially in increasing the income of farmers in Vietnam. Race et al (2019) stated that forests contribute 29% of the total income of community forest farmers in Indonesia.…”
Section: Trusted Stakeholders Of Community Forest Farmersmentioning
confidence: 99%
“…Thus, forest utilization reflects, to some degree, the importance of forests to farmers' livelihoods, which is inherently measured by the proportion of forest income in the total household income. In many uplands, the contribution of forests to livelihoods often accounts for a high share of total household income [3,4,29,30]. Forest utility is a measure of satisfaction that could encourage or hinder farmers from engaging in forest practices, depending on the degree to which their outcome exceeds expectations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…According to the Food and Agriculture Organization (FAO) (2015) [1], forest products are a major source of livelihoods for around 1.3 billion people, 18% of the world population. Poor people, especially destitute ones, utilize forest resources in various ways, ranging from agricultural inputs, subsistence, and fuelwood, to income [2][3][4][5][6]. More importantly, forests can facilitate poverty alleviation and inequality mitigation in many parts of the world [7].…”
Section: Introductionmentioning
confidence: 99%